Model Konvensional Satu Titik untuk Mengoptimalkan Masalah Transportasi Fuzzy Trapesium - Mujtaba, A; Syariah, Ai Munirotusy; Patimah, Ain Fitriyani; Wulan, Elis Ratna (KUBIK: Jurnal Publikasi Ilmiah Matematika, 2024)
Solving fuzzy trapezoidal transportation problem can use a one-point approach to obtain the optimal solution. The one-point method transforms the four points of the trapezoidal number into crisp transportation problems. This method comes with a minimum approach of supply and demand. In the end, these solutions are combined to obtain the optimal solution. The modified distribution is applied to each crisp problem to develop an optimal solution. The presented scheme is compared with competitive methods available in the literature and found to have good coordination with these methods.Â 